The Closet - An ethnological inquiry into the daily repetitive activity of clothing the body - Steinunn Viðar Sigurðardóttir 1960- (2024)
Clothing is more than just fabric and stitches; it reflects our identity,articulates our origin, and serves as a compass for navigating the world with our clothed bodies. Our closets, where we keep our clothing, are uniquely valued, like keys that unlock parts of our personality. The closet, the most private and personal space, guards the most intimate part of our existence, our second skin; it serves as a repository where we store the costumes for the everyday theatre of our lives. The impact of the simple daily habit of clothing one's body is profound and should not be overlooked. It is a routine that begins in early childhood and persists throughout our lives. This study sheds light on the meaning and value of clothing; it helps to understand how clothing influences and reflects personal identity. The sensory dimension, often neglected yet vital in our engagement with clothing, is a primary focus. Wearing clothing transcends mere visual perception; it involves internal experiences like comfort, tactile sensations, and the overall feel of the garment. The aim is to capture and break down into particles the entire process of clothing one's body, to analyze these elements and discuss the influence that clothing has on the individual; hence, the study's multifaceted results. This thesis is in partial fulfilment of the requirements for an MA degree in Folkloristics/Ethnology at the University of Iceland and is for 60 ECTS credits. It is based in the qualitative research tradition and builds on in-depth interviews, objective coding, and field notes. The thesis also incorporates sensory ethnography, a method that relates sensory data to emotions and feelings within clothing, providing a unique perspective on the topic. The data for this study was collected through interviews with a carefully selected group of ten high-profile figures within the high fashion industry in New York City. Their extensive experience and knowledge uniquely position them to provide insight into the cultural and social phenomenon known as ...